Efficacy and Safety of NTrap® Stone Entrapment and Extraction Device for Ureteroscopic Lithotripsy - Jiang, Kehua; Male, Musa; Yu, Xiao; Chen, Zhiqiang; Sun, Fa; Yuan, Huixing (Urology Journal, 2020)
Purpose: NTrap® stone entrapment and extraction device (NTrap®) is a device used to extract and remove stones from the urinary tract and to minimize retrograde stone migration during ureterolithotripsy (URS). This study aimed to evaluate the efficacy and safety of NTrap® in URS. Methods: From Jan 2014 to June 2017, 148 patients underwent URS with the aid of NTrap® (Group A), and 209 patients underwent standard URS without any anti-retropulsion device (Group B). Their demographics, operation time, complications, stone migration rate, and stone-free rate (SFR) were recorded for comparison. Results: Compared with group B, Group A had a significantly shorter operative and lasering time (P = 0.003, P<0.001, respectively). There was no significant difference between the 2 groups in overall complications, a decrease in mean hemoglobin, and length of stay (LOS) (P = 0.426, P = 0.097, P = 0.058, respectively). The incidence of stone migration was significantly lower in Group A than Group B (P = 0.035). The postoperative auxiliary procedure rate (in patients with stones retropulsion during the operation) was significantly lower in Group A compared to Group B (P = 0.024). The SFR was considerably higher in Group A than Group B (P = 0.009). Conclusion: URS, with the aid of NTrap®, is an effective and safe method for treating ureteric stones. It may prevent stones from retropulsion and shorten the operative time.